IPython interactive computing and visualization cookbook : over 100 hands-on recipes to sharpen your skills in high-performance numerical computing and data science with Python /: over 100 hands-on recipes to sharpen your skills in high-performance numerical computing and data science with Python. (2018) - Unknown
No abstract available